2022
DOI: 10.1002/term.3291
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA long intergenic non‐protein coding RNA 1232 promotes cell proliferation, migration and invasion in bladder cancer via modulating miR‐370‐5p/PIM3 axis

Abstract: Increasing evidences have suggested that long non‐coding RNAs are critical regulators in the progression of tumor growth. Long intergenic non‐protein coding RNA 1232 (LINC01232) was verified as an oncogene in multiple cancers. Nevertheless, its function in bladder cancer (BC) remains to be uncovered. In the current study, we detected LINC01232 expression utilizing quantitative real‐time polymerase chain reaction (RT‐qPCR) and discovered that LINC01232 was overexpressed in BC cell lines versus normal cell line.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As an example, Sang et al have observed the downregulation of miR-370-5p in breast cancer, and have experimentally confirmed that miR-370-5p overexpression represses proliferation and invasion of cancer cells. Intriguingly, miR-370-5p can obstruct bladder cancer cells to proliferate, migrate, and invade [ 14 ]. Moreover, downregulating miR-370-5p induces proliferative and invasive actions of colorectal carcinoma cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Sang et al have observed the downregulation of miR-370-5p in breast cancer, and have experimentally confirmed that miR-370-5p overexpression represses proliferation and invasion of cancer cells. Intriguingly, miR-370-5p can obstruct bladder cancer cells to proliferate, migrate, and invade [ 14 ]. Moreover, downregulating miR-370-5p induces proliferative and invasive actions of colorectal carcinoma cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The correct identification of the potential interaction between circRNAs and miRNAs improves the insight into disease pathogenesis, as well as provides a niche for diagnosing and managing the disease [ 11 ]. miR-370-5p has been widely accepted as a tumor suppressor [ 12 14 ]. Definitely, the action of miR-370-5p in RCC progression, especially in the field of glycolysis, is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Other research indicates that LINC01232 sequesters microRNA (miRNA)-654-3p and consequently promotes hepatoma-derived growth factor expression to contribute to the tumor progression in esophageal squamous cell carcinoma (28). Moreover, LINC01232 has been proven to promote cell proliferation, migration, and invasion by modulating the miR-370-5p-PIM3 axis in bladder cancer (29). Interestingly, AL031985.…”
Section: Discussionmentioning
confidence: 99%
“…Other research indicates that LINC01232 sequesters microRNA (miRNA)-654-3p and consequently promotes hepatoma-derived growth factor expression to contribute to the tumor progression in esophageal squamous cell carcinoma ( 28 ). Moreover, LINC01232 has been proven to promote cell proliferation, migration, and invasion by modulating the miR-370-5p–PIM3 axis in bladder cancer ( 29 ). Interestingly, AL031985.3 has been included in several lncRNA-based signatures related to ferroptosis, pyroptosis, immune, and autophagy in predicting the outcome, immune cell infiltration, and response to immunotherapy in patients with LIHC ( 30 - 33 ).…”
Section: Discussionmentioning
confidence: 99%